Remedy of contamination of multidrug resistant Salmonella and Escherichia coli from betel leaves (Piper betle) keeping them fresh for long time - Kamal, Tazrin; Nazir, K. H. M. Nazmul Hussain; Parvej, Md. Shafiullah; Rahman, Md. Tanvir; Rahman, Marzia; Khan, Mohammad Ferdousur Rahman; Ansari, Wahedul Karim; Ahamed, Md Mostakin; Ahmed, Sultan; Hossen, Md. Liakot; et al. (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was carried out to identify the associated Salmonella and Escherichia coli in betel leaves (Piper betle), and to develop an effective method to remove those microbes. Materials and methods: Betel leaves were collected from local and whole sale markets, and borouj (cultivation place). Salmonella and E. coli were isolated and identified by cultural, morphological, and biochemical tests followed by confirmation by polymerase chain reaction (PCR) targeting the genus specific 16S rRNA genes. Antibiogram of the isolated bacteria was performed by disc diffusion method. Different concentrations of Salmosan-A Soln were used to remediate the contaminating bacteria keeping the quality of betel leaves for longer periods. Results: Total Salmonella counts in the betel leaves were 3.9×105, 4.9×106, 3.5×104, 1.1×103 and 1.5×103 CFU/mL, while E. coli counts were 5.5×107, 6.3×107, 4.4×105, 3.3×103 and 3.1×103 CFU/mL in the betel leaves collected from K.R. market, Kewatkhali Bazaar, whole sale market, borouj in Kushtia and borouj in Natore, respectively. Antibiogram study revealed that the isolated bacteria were sensitive to doxycyclline, ciprofloxacin, chloramphenicol and cefotaxime. Application of 0.3% Salmosan-A Soln was found to be the most effective and suitable, where <1 CFU/mL in the betel leaves could be detected after treatment for 10 min. Conclusion: Results of this study indicated that treatment with 0.3% Salmosan-A Soln for 10 min is capable of removing Salmonella and E. coli from betel leaves keeping the treated leaves fresh up to 7 days of post-treatment. Method developed in this study can be adapted to reduce bacterial contamination of betel leaves more effectively in Bangladesh and other betel leaf exporting countries. http://doi.org/10.5455/javar.2018.e250